Potential medication interactions at a psychiatric emergency service of a general hospital: analysis of the first twenty-four hours - Oliveira, Luisa Parra; Zago, Karine Santana de Azevedo; Aguiar, Sheylla Bezerra (SMAD Revista Eletrônica Saúde Mental Álcool e Drogas (Edição em Português), 2015)
The objective in this study was to survey the potential pairs of drug interactions administered at the same time at a psychiatric emergency service of a general hospital during the first twenty-four hours of care. A descriptive, exploratory, documentary, retrospective and quantitative study was undertaken. The population relates to the histories of patients attended at the emergency service of the HCU-UFU, in the specialty area psychiatrics, in 2012. In total, 725 histories were selected of patients who visited the emergency service of the Hospital de Clínicas at Universidade Federal de Uberlândia in 2012. The possible drug interactions were analyzed based on the crossing of the drugs in the databases Drugs® and Micromedex®. The most frequent interaction in the histories analyzed was Haloperidol + Promethazine, totaling 17.7% of all 1,537 pairs of drugs administered at the same time during the research period. The database Drugs® informed that, of all pairs administered during that period, 559 (36%) presented possible interactions, while 978 (64%) had no signs of interaction risk. Micromedex® evidenced that, in 329 (21%) of the drug pairs administered, some type of drug interaction took place while, in 1,208 (79%) pairs, no interaction possibility was found. The predominant drug classes of possible interactions were Benzodiazepines + Antipsychotics, an association commonly used in psychiatric emergencies, alerting to the need to monitor the possible adverse effects of these drugs. Based on the findings, a figure was elaborated with the main care for possible interactions between drugs used in psychiatric emergency care.